Influence of the dopaminergic system, CREB, and transcription factor-B on cocaine neurotoxicity - Planeta, Cleopatra da Silva [UNESP] (2013)
Cocaine is a widely used drug and its abuse is associated with physical, psychiatric and social problems. Abnormalities in newborns have been demonstrated to be due to the toxic effects of cocaine during fetal development. The mechanism by which cocaine causes neurological damage is complex and involves interactions of the drug with several neurotransmitter systems, such as the increase of extracellular levels of dopamine and free radicals, and modulation of transcription factors. The aim of this review was to evaluate the importance of the dopaminergic system and the participation of inflammatory signaling in cocaine neurotoxicity. Our study showed that cocaine activates the transcription factors NF-κB and CREB, which regulate genes involved in cellular death. GBR 12909 (an inhibitor of dopamine reuptake), lidocaine (a local anesthetic), and dopamine did not activate NF-κB in the same way as cocaine. However, the attenuation of NF-κB activity after the pretreatment of the cells with SCH 23390, a D1 receptor antagonist, suggests that the activation of NF-κB by cocaine is, at least partially, due to activation of D1 receptors. NF-κB seems to have a protective role in these cells because its inhibition increased cellular death caused by cocaine. The increase in BDNF (brain-derived neurotrophic factor) mRNA can also be related to the protective role of both CREB and NF-κB transcription factors. An understanding of the mechanisms by which cocaine induces cell death in the brain will contribute to the development of new therapies for drug abusers, which can help to slow down the progress of degenerative processes.